Efektifitas dan Benefit Incidence Analysis Kebijakan Pupuk Bersubsidi di Kecamatan Wedung Kabupaten Demak - Fadil Mufid Kurnia; Evi Yulia Purwanti (Diponegoro Journal of Economics, 2020)
The agricultural sector has an important role in the Demak Regency. To support the agricultural sector, the government has supported various forms of policy. One of them is the policy of subsidized fertilizer. The purpose of this study was to determine the effectiveness and accuracy of the distribution of benefits from the policy of subsidized fertilizers in the Subdistrict of Wedung, Demak Regency. This study uses a quantitative descriptive method with four precise indicators to determine effectiveness, and uses the Benefit Incidence Analysis (BIA) method to determine the distribution of benefits from the policy. Based on the results of the study, the policy in Wedung cannot be said to be effective. As for the indicators price, time and quantity are not yet effective. Distribution of benefits from the program received by small farmers are only 4.9 percent, so the policy can be said to be a regressive policy.